Bone Stress-Strain State Evaluation Using CT Based FEM - Gerasimov, Oleg V.; Kharin, Nikita V.; Fedyanin, Artur O.; Bolshakov, Pavel V.; Baltin, Maxim E.; Statsenko, Evgeny O.; Fadeev, Filip O.; Islamov, Rustem R.; Baltina, Tatyana V.; Sachenkov, Oskar A. (Frontiers in Mechanical Engineering, 2021)
In the article, the CT-based FEM solution is introduced. A three-dimensional isoparametric linear element of a continuous medium, built on the basis of computed tomography data was used. The general algorithm to get the FE model is presented. CT data and region of interest are enough to build a calculation-ready model. The simulation easy done after boundary conditions applied. For this purpose computational and post-processing grids were introduced. The quality of simulation can be estimated by normalized error. The Fore and hind limbs were used for three-point bending simulation. Additionally, three-point bending experiments were held. Achieved results were compared and they illustrate the effectiveness of the method. The proposed method illustrates a not laborious and time-efficient approach.